Effect of flue gas CO2 on the growth, carbohydrate and fatty acid composition of a green microalga Scenedesmus obliquus for biofuel production. Issue 16 (18th August 2017) - Ji, Min-Kyu; Yun, Hyun-Shik; Hwang, Jae-Hoon; Salama, El-Sayed; Jeon, Byong-Hun; Choi, Jaeyoung
ABSTRACT: Effect of various flue gas CO2 concentrations (5%, 10% and 14.1%) on growth rate and biochemical properties of a green microalga Scenedesmus obliquus was investigated. S. obliquus showed the highest biomass production and growth rate (0.36 g L −1 and μ max  = 1.00 day −1 ), total inorganic carbon removal (35.8 mg L −1 ), lipid productivity (9.9 mg L −1  day) and carbohydrate productivity (10.3 mg L −1  day) with 14.1% CO2 after 8 days of cultivation. Fatty acid methyl ester analysis revealed that the palmitic and oleic acid contents were increased up to 5% and 7% with 14.1% CO2, respectively. Application of flue gas CO2 enhanced the growth along with lipid and carbohydrate productivity of S. obliquus, which can be exploited for reducing the CO2 concentration.